Psychosocial risk factors for cardiovascular disease: vital exhaustion and its associations with biochemical markers of inflammation among persons 25-44 years old - V. V. Gafarov; E. A. Gromova; E. V. Kashtanova; D. V. Denisova; I. V. Gagulin; Y. V. Polonskaya; A. V. Gafarova; Yu. I. Ragino (Российский кардиологический журнал, 2024)
Aim. To study the association of interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and monocyte chemoattractant protein-1 (MCP-1) levels with vital exhaustion (VE) among men and women aged 25-44 years in Novosibirsk.Material and methods. At the Research Institute of Internal and Preventive Medicine (Novosibirsk), during 2013-2016, a cross-sectional survey of a random representative sample of people aged 25-44 years in one of the typical districts of Novosibirsk was carried out. A total of 975 individuals were examined (403 men, 530 women). The response rate was 71%. General examination and history collection were carried out according to standard methods included in the WHO program "MONICA-psychosocial (MOPSY)". All study participants completed the Maastricht Vital Exhaustion Questionnaire (MQ).Results. High and medium VE prevailed among women (15,7% and 40,6%) than among men (5,5% and 32,8%) (p<0,001). Median serum levels of IL-6 were high VE among both sexes 1,41 [0,70;4,60] pg/ml, compared with medium VE 1,20 [0,65;2,90] pg/ml, and low VE 1,12 [0,58;2,32] pg/ml (p<0,01), and among women with high VE 1,53 [0,72;4,33] pg/ml, compared with medium VE 1,14 [0,63;2,36] pg/ml and low VE 0,95 [0,50;1,98] pg/ml (p<0,05). Serum TNF-α was higher among women with high VE (6,01±3,23 pg/ml) than with medium VE (5,63±4,16 pg/ml) and low VE (4,95±2,85 pg/ml) (p=0,025). Mean serum MCP-1 levels among both sexes, men and women, were higher with high VE (324,55±161,89 pg/ml, 270,75±107,92 pg/ml and 338,81±171,1 pg/ml) than with medium (251,78±123,4 pg/ml, 262,46±134,9 pg/ml and 245,22±115,61 pg/ml), and low VE (227,59±101,03 pg/ml, 234,51±104,53 pg/ml and 220,17±96,81 pg/ml) (p<0,001).Conclusion. An increase in the average levels of inflammation biochemical markers (IL-6, TNF-α, MCP-1) was established in individuals 25-44 years old with a high VE.